Clonal heterogeneity in ER+ breast cancer reveals the proteasome and PKC as potential therapeutic targets - Beumers, Lukas; Vlachavas, Efstathios-Iason; Borgoni, Simone; Schwarzmüller, Luisa; Penso-Dolfin, Luca; Michels, Birgitta E.; Sofyali, Emre; Burmester, Sara; Heiss, Daniela; Corban-Wilhelm, Heike; Yarden, Yosef; Helm, Dominic; et al. (npj Breast cancer, 2023)
Intratumoral heterogeneity impacts the success or failure of anti-cancer therapies. Here, we investigated the evolution and mechanistic heterogeneity in clonal populations of cell models for estrogen receptor positive breast cancer. To this end, we established barcoded models of luminal breast cancer and rendered them resistant to commonly applied first line endocrine therapies. By isolating single clones from the resistant cell pools and characterizing replicates of individual clones we observed inter- (between cell lines) and intra-tumor (between different clones from the same cell line) heterogeneity. Molecular characterization at RNA and phospho-proteomic levels revealed private clonal activation of the unfolded protein response and respective sensitivity to inhibition of the proteasome, and potentially shared sensitivities for repression of protein kinase C. Our in vitro findings are consistent with tumor-heterogeneity that is observed in breast cancer patients thus highlighting the need to uncover heterogeneity at an individual patient level and to adjust therapies accordingly.
Gesehen am 29.01.2024